PELAKSANAAN PENGELOLAAN SAMPAH DI KOTA PEKANBARU TAHUN 2020 - Tri Angga Rahmadhani. S; Erman M (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2022)
The implementation of waste management is a systematic, comprehensive and sustainable activity that includes waste reduction and handling. Waste management is a complex problem and requires handling with many disciplines. Waste management is currently seen as only the responsibility of the government. The community plays a role only as the party being served, because they feel that it is enough just to pay the waste retribution so that further handling is the responsibility of the government. Government management efforts in planning, organizing, implementing and supervising programs or activities related to waste in order to realize cleanliness and beauty in the city of Pekanbaru, but these efforts have not been supported by the availability of facilities and infrastructure related to the waste transportation unit, thus causing waste problems. what happened in the city of Pekanbaru. The purpose of this study is to determine the implementation of waste management in Pekanbaru City in 2020, especially for zone three, where zone three is managed directly by the Pekanbaru City Environment and Hygiene Service and what are the inhibiting factors. This research uses descriptive qualitative technique. In collecting data, the author uses interview and documentation techniques. The results of this study conclude that waste management in Pekanbaru City, especially for zone three, has not been implemented optimally. This is known from the fact that there are still problems related to waste problems that have not been processed directly, resulting in piles of garbage and cannot be processed effectively. there are still problems found in the field due to several factors, lack of adequate human resources in terms of quantity and quality, then infrastructure that is not supported by equipment maintenance and repair activities. So that the implementation of waste management activities in Pekanbaru City, especially zone three, cannot be realized to the maximum which indirectly causes a pile of garbage. Keywords : Implementation, Management, Waste Management